An analytical method for calculating the natural frequency of reinforced retaining walls with soil–structure interaction effect. Issue 1 (February 2014) - Abbasi, O.; Ghanbari, A.; Hosseini, S.A.A.
Abstract : ABSTRACT: Natural frequency is one of the most important parameters in the seismic behaviour of structures, including retaining walls. In this study the theory of beams on elastic foundations and the energy method were used to obtain a precise analytical formulation for the natural frequency of the fundamental mode of geosynthetic-reinforced soil-retaining walls. The assumed retaining wall was reinforced with full-height rigid concrete facing (GRS-FHR walls). Moreover, use of the suggested formula facilitates the consideration of soil and wall interaction in calculating natural frequency. The backfill and foundation soil of the retaining wall were modelled using translational springs. The result obtained from the suggested formula was compared with the result of numerical analysis using ANSYS software, and a good agreement was found.